2020
DOI: 10.36713/epra4022
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Trust in Online Purchase Decision

Abstract: Trust plays an important role in online purchasing. Trust issues that arise in online purchasing occur since consumers cannot verify the product directly. This study aims to analyze the antecedents of trust in terms of online purchase decision and analyze the effect of trust on online purchase decision. The sampling technique used in this study was purposive sampling. The total sample of 120 respondents in Jakarta was obtained through the distribution of online questionnaires. The data analysis method used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 12 publications
8
30
1
15
Order By: Relevance
“…Trust could make people willing to exchange their personal information for the brand (Rahman et al, 2020). Several studies have shown that trust has a positive impact on purchase decisions (Prasad et al, 2017;Oghazi et al, 2018;Mahliza, 2020). Therefore, the third hypothesis proposed is:…”
Section: Literature Review and Hypotheses Proposedmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust could make people willing to exchange their personal information for the brand (Rahman et al, 2020). Several studies have shown that trust has a positive impact on purchase decisions (Prasad et al, 2017;Oghazi et al, 2018;Mahliza, 2020). Therefore, the third hypothesis proposed is:…”
Section: Literature Review and Hypotheses Proposedmentioning
confidence: 99%
“…With trust, both consumers and sellers could make a transaction more secure, more safe, and more convenient without any suspicion from both parties (Widodo et al, 2017). Several research studies have shown that trust is affecting and influencing purchase decisions (Prasad et al, 2017;Oghazi et al, 2018;Puspitasari et al, 2018;Mahliza, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The third hypothesis in this study stated that brand trust had a direct significant influence on the college decision is accepted. Building brand trust can be done (Juhaeri, 2018)(Chao, 2019) (Mahliza, 2020). The trust from candidate new students is important thing before providing the expected value of students.…”
Section: Figure 3: Results Of Research Data Processingmentioning
confidence: 99%
“…In an e-commerce environment, consumer trust is the most important part of the success factor [13,26,27,28]. Several studies show that online trust influences online purchasing decisions [29,30,31,32], intention to buy [33], satisfaction [34], and customer loyalty [35,36,37]. Trust is also the main key to building relationships with consumers [38].…”
Section: Literature Reviewmentioning
confidence: 99%